Effects of Luteinizing Hormone Releasing Hormone A2 on Gonad Development in Juvenile Amur Sturgeon, Acipenser schrenckii, Revealed by Transcriptome Profiling Analysis - Lv, Weihua; Jin, Shubo; Cao, Dingchen; Wang, Nianmin; Jin, Xing; Zhang, Ying (Frontiers in Genetics, 2022)
Acipenser schrenckii is an economically important aquatic species whose gonads require particularly long times to reach sexual maturity. Luteinizing hormone plays important roles in gonad development, and luteinizing hormone releasing hormone A2 (LH-A2) is used as an oxytocin to promote ovulation in aquaculture of A. schrenckii. In this study, we aimed to determine the effects of LH-A2 on gonad development in juvenile A. schrenckii through transcriptome profiling analysis of the pituitary and gonads after LH-A2 treatment at a dose of 3 μg/kg. The 17β-estradiol (E2) levels gradually increased with LH-A2 treatment time, and significantly differed from those of the control group on days 5 and 7 (p < 0.01). However, the content of testosterone (Testo) gradually decreased with LH-A2 treatment time and showed significant differences on day 3 (p < 0.05), and on days 5 and 7 (p < 0.01), compared to those in the control group. Thus, LH-A2 promotes the secretion of E2 and inhibits the secretion of Testo. Transcriptome profiling analysis revealed a total of 2,883 and 8,476 differentially expressed genes (DEGs) in the pituitary and gonads, respectively, thus indicating that LH-A2 has more regulatory effects on the gonads than the pituitary in A. schrenckii. Signal transduction, global and overview maps, immune system, endocrine system and lipid metabolism were the main enriched metabolic pathways in both the pituitary and gonads. Sixteen important genes were selected from these metabolic pathways. Seven genes were co-DEGs enriched in both signal transduction and endocrine system metabolic pathways. The other co-DEGs were selected from the immune system and lipid metabolism metabolic pathways, and showed mRNA expression changes of > 7.0. The expression of five DEGs throughout LH-A2 treatment was verified to show the same patterns of change as those observed with RNA-seq, indicating the accuracy of the RNA-seq in this study. Our findings provide valuable evidence of the regulation of gonad development of juvenile A. schrenckii by LH-A2 and may enable the establishment of artificial techniques to regulate gonad development in this species.